+0  
 
0
534
1
avatar+33 

(1/2)^2+(-2)^2/2^3

 Nov 28, 2014

Best Answer 

 #1
avatar+128393 
+13

(1/2)^2+ [(-2)^2/2^3] =

(1/2)*(1/2) + [(-2)*(-2)/(2*2*2)] =

(1/4)          +   [ 4       /   8]          remember we perform any multiplications/divisions from left to right, frst, before additions/subtractions

(1/4)           +     1/2         common denominator

(1/4)            +    (2/4)    =

3/4

 

 Nov 28, 2014
 #1
avatar+128393 
+13
Best Answer

(1/2)^2+ [(-2)^2/2^3] =

(1/2)*(1/2) + [(-2)*(-2)/(2*2*2)] =

(1/4)          +   [ 4       /   8]          remember we perform any multiplications/divisions from left to right, frst, before additions/subtractions

(1/4)           +     1/2         common denominator

(1/4)            +    (2/4)    =

3/4

 

CPhill Nov 28, 2014

3 Online Users

avatar